Identification of Periosteal Osteogenic Progenitors in Jawbone. (August 2022) - Ding, Y.; Mo, C.; Geng, J.; Li, J.; Sun, Y.
Unlike long bones, jawbone development is mainly accomplished by intramembranous ossification resulting from the differentiation of periosteal progenitor cells. However, the spatiotemporal ontogeny of periosteal progenitor cells during jawbone development and repair remains elusive. In this study, we mapped the transcriptional landscape of the human jawbone periosteum at single-cell resolution and identified a cathepsin K (Ctsk) + periosteal subset. Lineage tracing analysis indicated that Ctsk-Cre–labeled periosteal cells could make contributions to jawbone development. However, different from the periosteal-specific location of Ctsk + cells in long bone, we also identified Ctsk + stromal cells in jawbone marrow and implied the heterogeneity of jawbone Ctsk + hierarchy. In further analysis of the periosteal progenitor cell subset of heterogeneous Ctsk + hierarchy, we identified a unique Ctsk + Ly6a + subset of cells. The additional marker Ly6a helped to further confine the progenitor subset to the jawbone periosteum and was nearly undetectable in the bone marrow. Defects in the jawbone could activate the migration and osteogenic differentiation of Ctsk + Ly6a + cells. Local ablation of Ctsk + cells by diphtheria reduced the number of Ctsk + Ly6a + cells and delayed the repair of the bone defect. Taken together, we identify a novel periosteal osteogenic progenitor subset that is active in jawbone osteogenesis and healing.